2019
DOI: 10.1089/neu.2017.5450
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Injury Leads to Inflammation and Altered Tryptophan Metabolism in the Juvenile Rabbit Brain

Abstract: Neuroinflammation after traumatic brain injury (TBI) contributes to widespread cell death and tissue loss. Here, we evaluated sequential inflammatory response in the brain, as well as inflammation-induced changes in brain tryptophan metabolism over time, in a rabbit pediatric TBI model. On post-natal days 5-7 (P5-P7), New Zealand white rabbit littermates were randomized into three groups: naïve (no injury), sham (craniotomy alone), and TBI (controlled cortical impact). Animals were sacrificed at 6 h and 1, 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 115 publications
0
27
0
Order By: Relevance
“…Recent findings reveal that TBI reduces reuptake of 5-HT via modulation of the serotonin transporter (SERT) to prevent replenish of neuronal stores of 5-HT and consequently serotonergic transmission [129]. It has been shown that TBI-induced neuroinflammation decreases serotonin/tryptophan ratio at 21 days post-injury [130]. Overall, preclinical evidence suggests that 5-HT neurotransmission is decreased over time, contributing to the manifestation or worsening of neuropsychological symptoms.…”
Section: Serotonin (5-hydroxytryptamine 5-ht)mentioning
confidence: 99%
“…Recent findings reveal that TBI reduces reuptake of 5-HT via modulation of the serotonin transporter (SERT) to prevent replenish of neuronal stores of 5-HT and consequently serotonergic transmission [129]. It has been shown that TBI-induced neuroinflammation decreases serotonin/tryptophan ratio at 21 days post-injury [130]. Overall, preclinical evidence suggests that 5-HT neurotransmission is decreased over time, contributing to the manifestation or worsening of neuropsychological symptoms.…”
Section: Serotonin (5-hydroxytryptamine 5-ht)mentioning
confidence: 99%
“…The developing brain may have a particularly unique inflammatory response after TBI, given the normal role that microglia play in brain development and homeostasis, their location in white matter tracts in early development, and the relative pro-inflammatory phenotype of microglia in the young brain (Pierre et al, 2017, Bhalala, Koehler andKannan., 2015). There is relatively strong evidence for neuroinflammation after pediatric TBI in both animal and human studies (Cederberg and Siesjo., 2010, Merkel et al, 2017, Moretti et al, 2016, Zhang et al, 2018, Hanlon, Raghupathi and Huh., 2017, Schober et al, 2016, Newell et al, 2015, including a series of studies from Pittsburgh delineating the profile of inflammatory markers in the cerebrospinal fluid of infants and children after TBI (Newell et al, 2015, Buttram et al, 2007, Walko et al, 2014, Wallisch et al, 2017.…”
Section: Convergence Of Sex Differences and Tbimentioning
confidence: 99%
“…In pathologic conditions, such as following TBI, tryptophan metabolism can shift from producing protective and homeostatic products, such as serotonin, melatonin, and kynurenic acid, to producing excitotoxic products, such as quinolinic acid (reviewed in (Palego et al, 2016)). This can be especially true in the setting of robust neuroinflammation, and evidence for this metabolic shift is seen in animal and human TBI studies (Sinz et al, 1998, Meier et al, 2016, Chung et al, 2009, including pediatric TBI (Zhang et al, 2018, Bell et al, 1999, Berger et al, 2004. Furthermore, there is emerging literature that sex hormones can influence the tryptophan pathway (Barth, Villringer and Sacher., 2015), which could be an important consideration in adolescent victims of TBI.…”
Section: Convergence Of Sex Differences and Tbimentioning
confidence: 99%
“…Tryptophan is also the precursor for neurotransmitters serotonin and melatonin, which are important in regulating mood and sleep (104). Our group has shown that CCI in infant rabbits upregulates IDO1 in microglia, acutely increases kynurenine levels, and decreases serotonin and melatonin at later time points (104). These findings point to a link between microglial activation, tryptophan metabolism, and the long-term sequelae of mood and sleep dysregulation after pediatric TBI.…”
Section: Amino Acid Metabolismmentioning
confidence: 96%
“…Modulating the relative activity of neuroprotective kynurenine aminotransferase vs. neurotoxic kynurenine 3-monooxygenase may be beneficial for attenuating inflammation. Tryptophan is also the precursor for neurotransmitters serotonin and melatonin, which are important in regulating mood and sleep (104). Our group has shown that CCI in infant rabbits upregulates IDO1 in microglia, acutely increases kynurenine levels, and decreases serotonin and melatonin at later time points (104).…”
Section: Amino Acid Metabolismmentioning
confidence: 99%